2003
DOI: 10.1073/pnas.0434905100
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial enterotoxins are associated with resistance to colon cancer

Abstract: One half million patients suffer from colorectal cancer in industrialized nations, yet this disease exhibits a low incidence in underdeveloped countries. This geographic imbalance suggests an environmental contribution to the resistance of endemic populations to intestinal neoplasia. A common epidemiological characteristic of these colon cancer-spared regions is the prevalence of enterotoxigenic bacteria associated with diarrheal disease. Here, a bacterial heat-stable enterotoxin was demonstrated to suppress c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
223
2
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(232 citation statements)
references
References 40 publications
4
223
2
3
Order By: Relevance
“…GC-C is known to signal via both cGMP and calcium, 2,6,[31][32][33] although these pathways have not been fully explored with regard to proliferation and apoptosis. We have shown that there is an approximately 2-fold decrease in mucosal cGMP levels in GC-C-deficient Apc Min/1 mice compared to Apc Min/1 ; Gucy2c 1/1 mice ( Table I).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GC-C is known to signal via both cGMP and calcium, 2,6,[31][32][33] although these pathways have not been fully explored with regard to proliferation and apoptosis. We have shown that there is an approximately 2-fold decrease in mucosal cGMP levels in GC-C-deficient Apc Min/1 mice compared to Apc Min/1 ; Gucy2c 1/1 mice ( Table I).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that ST exposure activates calcium influx through cyclic nucleotide-gated channels in rat colonocytes 6 and in T84 cells, where it is associated with decreased proliferation. 2 However, mice lacking GC-C, Gucy2c 2/2 , are viable and fertile with no apparent defects in intestinal morphology or growth 7,8 and there are no differences in crypt depth or villus height (data not shown). Functional studies established that while colonic ion transport is similar to that observed in wild-type mice, 9 bicarbonate secretion in the duodenum of GC-C null mice is greatly attenuated in response to acid, a major physiologic stimulus of secretion.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Además, las ST tienen la capacidad de controlar la proliferación celular. Según estudios, inhibe la síntesis de ADN en células de cáncer de colon, que depende de los niveles de calcio intracelulares (Figura 3) 79,80 . La citolisina A (ClyA: cytolysin A) expresada del gen clyA también ha sido descrita como citotoxina de ECET cuyas funciones son la formación de poros, inducción de apoptosis en los macrófagos y actividad hemolítica [81][82][83] .…”
Section: Patogeniaunclassified
“…Although the epidemiology of colon cancer remains poorly understood, there is clearly an unexplained inverse relationship between the incidence of colorectal cancer and enterotoxigenic Escherichia coli (ETEC) infections (3,4). Drawing from these observations, Pitari et al (5) introduced an interesting hypothesis that specific peptides (STa) elaborated from ETEC may prevent the hyperproliferative and neoplastic development of intestinal epithelial cells that are associated with initiation and progression of colorectal cancer. Although a direct causal relationship between STa-mediated infectious diarrhea and low cancer rates in under-developed countries has not been proven, the authors provide convincing evidence of the presence of a novel intracellular signaling pathway initiated by STa that prevents proliferation of colon cancer cells.…”
mentioning
confidence: 99%